RETRACTED: The effect of salinity levels on certain physiological groups of microorganisms in irrigated soils of Bukhara region - Umarov Otabek; Bafayeva Zahro; Avezov To`lqinjon (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001